Gribov's confinement scenario - Ewerz, Carlo (Nuclear physics. Proceedings supplements, 2001)
I give a brief account of Gribov's scenario of supercritical charges in QCD. Gribov's equation for the Green function of light quarks and its derivation from the corresponding Dyson-Schwinger equation are described. The resulting Green function is shown to exhibit chiral symmetry breaking.